FAKTOR PENYEBAB KONFORMITAS DALAM NOVEL KONBINI NINGEN - Bayu Rizkia Hidayat; Fenny Febrianty (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This research is motivated by the stigma or standards that are often encountered in certain community groups. The purpose of this study is to determine the form of conformity and the factors that influence the occurrence of conformity to the character Keiko Furukura in the novel Konbini Ningen by Sayaka Murata. The research method that author uses in this research is descriptive analysis method with a literary psychology approach. The main theory used in this research is the theory of conformity expressed by Myers and the supporting theory of conformity expressed by Sunarto and Prayitno. Then, to analyze the data, the author uses Sigmund Freud's theory of personality structure which relates to desire (id), good and bad considerations (superego) and the executor of these two things (ego) as well as characterization theory expressed by Nurgiyantoro to be linked with conformity in order to find solid conclusions. The data that became the object of the study were in the form of quotations from the form of conformity and the factors that influenced the occurrence of conformity in the character of Keiko Furukura. The data that became the object of research were in the form of quotations of conformity and factors that influenced the occurrence of conformity in the character of Keiko Furukura. The results of data analysis in this study concluded that there are two forms of conformity in Keiko Furukura's character, namely conformity of fulfillment and conformity of internalization, in conformity of fulfillment (superego) aspects is more dominant while in conformity of internalization (id) aspect is more dominant, then the factors that influence the occurrence of conformity in Keiko Furukura's character is group pressure and the influence of the person she likes. This research is expected to add insight to the reader about the phenomenon of conformity so that interactions in the social sphere can run more healthily. Keywords : conformity, konbini ningen, Japanese literature, novel